Mechanism of first-row transition metal nanoclusters formation and stabilization with highly ordered SBA-15 mesoporous materials - Yang, Yanhui (2010)
First-row transition metal catalysts are notoriously difficult to prepare and stabilize in very high dispersion which, in turn will affect the catalytic properties. We propose to design and synthesize SBA-15 mesoporous materials with physicochemical properties precisely controlled to stabilize the metallic nanoclusters under severe reaction conditions, i.e., the disproportionation of carbon monoxide. The study of the fundamental and molecular-level science, and mechanisms controlling the synthesis of the catalyst and the interaction between support and metal nanoclusters are envisioned. Extensive advanced characterization i.e., synchrotron light source X-ray absorption, will be carried out to investigate the mechanism of metal nanoparticles formation and stabilization. Most catalyst syntheses are conducted case by case, i.e., a matter of trial and error; there is a notable lack of reliable general methodologies. Only recently has there developed an interest in the exploration of catalyst synthesis in a more quantitative manner. A systematic approach by means of statistical modeling will be carried out to analyze the synthesis of SBA-15.